Molecular Interactions Studies Using Excess Thermodynamic Function in the Binary Mixtures of Cyclohexanol with Bromo, Chloro and Nitro Substituted Benzenes - Rajendirane, P.; Peri, S.; Govindan, K. (Asian Journal of Chemistry, 2010)
The molecular interactions operating in polar liquid mixtures can be studied conveniently by non-spectral methods, namely, excess thermodynamic quantities, as it reflects the solution dynamics and hence helps to understand the type and nature of molecular ineractions. Molar excess volume, excess viscosity, Gibbs' free energy change of viscous flow, interaction parameter and interaction energy for the binaries of bromobenzene, chlorobenzene and nitrobenzene with cyclohexanol at selected compositions were determined from the measured values of density and viscosity of pure liquids and their binaries at 303.15 K. FT-IR spectra at chosen composition of titled binaries were recorded with a view to substantiate the conclusion obtained from excess function investigations. Besides, an attempt is made to discern how the substituents present in the solvent molecule affect the solute-solvent interactions by different functional groups of polar aromatic compounds.